Using Ultrasound to Enhance Medical Students' Femoral Vascular Physical Examination Skills. (31st August 2015) - Ahn, Justin S.; French, Andrew J.; Thiessen, Molly E. W.; Browne, Vaughn; Deutchman, Mark; Guiton, Gretchen; Madigosky, Wendy; Kendall, John L.
Abstract : Objectives: To determine whether the addition of ultrasound to traditional physical examination instruction improves junior medical students' abilities to locate the femoral pulse. Methods: Initially, 150 second‐year medical students were taught the femoral pulse examination using traditional bedside teaching on standardized patients and online didactic videos. Students were then randomized into 2 groups: group 1 received ultrasound training first and then completed the standardized examination; and group 2 performed the standardized examination first and then received ultrasound training. On the standardized patients, the femoral artery was marked with invisible ink before the sessions using ultrasound. Compared to these markers, students were then evaluated on the accuracy of femoral artery pulse palpation and the estimated location of the femoral vein. All students completed a self‐assessment survey after the ultrasound sessions. Results: Ultrasound training improved the students' ability to palpate the femoral pulse ( P = .02). However, ultrasound did not facilitate correct estimation of the femoral vein's anatomic location ( P = .09). Confidence levels in localizing the femoral artery and vein were equal between groups at baseline, and both increased after the ultrasound sessions. Conclusions: The addition of ultrasound teaching to traditional physical examination instruction enhanced medical student competency and confidence with the femoral vascular examination. However, understanding of anatomy may require emphasis on precourse didactic material, but further study is required.